Last of the Black Titans - Wiggan, Greg. author. aut Link
Approx. 100 p.
Keywords: This book investigates the historical and contemporary role of Historically Black Colleges and Universities (HBCUs). In doing so, it provides a background on the pre-colonial entry of Africans into the Americas, as well as African educational traditions, and the struggles for education during the period of enslavement in North America. It discusses the social, historical and contemporary context that pertains to the development of Black education and the formation of HBCUs as a framework for the case study on African American college-bound students’ perceptions about attending an HBCU. Last of the Black Titans weaves in students’ perspectives regarding HBCUs and concludes with insights and recommendations regarding the future of these institutions. : 'Courier New'; ">size: 13.3333330154419px; ">Greg Wiggan is an Associate Professor of Urban Education, Adjunct Associate Professor of Sociology, and Affiliate Faculty Member of Africana Studies at the University of North Carolina at Charlotte. His research addresses urban education and urban sociology in the context of school processes that promote high achievement among African American students and other underserved minority student populations. In doing so, his research also examines the broader connections between the history of urbanization, globalization processes and the internationalization of education in urban schools. His books include: Global Issues in Education: Pedagogy, Policy, Practice, and the Minority Experience; Education in a Strange Land: Globalization, Urbanization, and Urban Schools –The Social and Educational Implications of the Geopolitical Economy; Curriculum Violence: America’s new Civil Rights Issue; Education for the New Frontier: Race, Education and Triumph in Jim Crow America 1867-1945; Following the Northern Star: Caribbean Identities and Education in North American Schools; Unshackled: Education for Freedom, Student Achievement and Personal Emancipation; and In Search of a Canon: European History and the Imperialist State. Lakia Scott is an Assistant Professor of Education in the Department of Curriculum and Instruction at Baylor University. Her research interests address urban education and student achievement. .